Answers
Answered by
1
Apply BODMAS rule, It states that We have to solve the Brackets first, Now,
The question is,
15 + (2-3-(2(5-4+1))),
=> We have to solve the inner brackets first, and then the outer Brackets,
The inner brackets sum = 5-4+1 = 1+1 = 2,
Now re-writing the question :
=> 15 + (2-3-(2(2))), Now 2 and 2 gets multiplied since there is no intermediate and symbols !,
=> 2*2 = 4, Re-writing the question again,
=> 15 + (2-3-(4)), Now - applies to the 4 and we need to solve the Brackets,
=> (2-3-4)[inner brackets sum] = -5, Now, Re-writing the question again,
=> 15 +(-5) , Opening the brackets and doing the sum,
=> 15 - 5 = 10,
Therefore the answer to your question is 10,
Hope you understand, Have a Great day ! Merry Christmas !
Thanking you, Bunti 360 !
The question is,
15 + (2-3-(2(5-4+1))),
=> We have to solve the inner brackets first, and then the outer Brackets,
The inner brackets sum = 5-4+1 = 1+1 = 2,
Now re-writing the question :
=> 15 + (2-3-(2(2))), Now 2 and 2 gets multiplied since there is no intermediate and symbols !,
=> 2*2 = 4, Re-writing the question again,
=> 15 + (2-3-(4)), Now - applies to the 4 and we need to solve the Brackets,
=> (2-3-4)[inner brackets sum] = -5, Now, Re-writing the question again,
=> 15 +(-5) , Opening the brackets and doing the sum,
=> 15 - 5 = 10,
Therefore the answer to your question is 10,
Hope you understand, Have a Great day ! Merry Christmas !
Thanking you, Bunti 360 !
Similar questions